Komorbid, Usia, dan Jenis Fraktur Ekstremitas Bawah Berhubungan dengan Lama Rawat Inap pada Pasien Post Open Reduction Internal Fixation (ORIF) - Aida Nuriyanti Putri; Rudi Hamarno; Tri Johan Agus Agus Yuswanto (FORIKES, 2023)
Fractures of the lower extremities are often associated with morbidity that can lead to prolonged hospital stays. Fractures can affect activity resistance and impaired mobility so that the wound healing process is prolonged. The aim of this study was to determine the relationship between comorbidities, age, location and type of lower extremity fracture with length of stay in post-ORIF patients. The research method was carried out with a retrospective design involving 73 patients selected using a purposive sampling technique. The collected data was then analyzed using the Spearman Rank and Chi-square correlation tests. The p value of the Spearman Rank test between comorbidities and length of stay for post-ORIF patients is 0.000. The p value of the Spearman Rank test between age and length of stay in post-ORIF patients is 0.000. The p value of the Chi-square test between the fracture location and the patient's length of stay after ORIF was 0.972. The p value of the Chi-square test between the type of fracture and the length of stay for post-ORIF patients was 0.031. It was concluded that there was a relationship between comorbidities, age, and type of fracture and length of stay in post-ORIF patients.Keywords: comorbid; age; fracture location; fracture type; length of hospitalization; post ORIF ABSTRAK Fraktur pada ekstremitas bawah sering dikaitkan dengan morbiditas yang dapat menyebabkan lama rawat inap di rumah sakit memanjang. Fraktur dapat mempengaruhi resistensi aktivitas dan gangguan mobilisasi sehingga proses penyembuhan luka memanjang. Tujuan penelitian ini adalah untuk mengetahui hubungan antara komorbid, usia, lokasi, dan jenis fraktur ekstremitas bawah dengan lama rawat inap pada pasien post ORIF. Metode penelitian dilaksanakan dengan rancangan restrospektif yang melibatkan 73 pasien yang dipilih dengan teknik purposive sampling. Data yang telah terkumpul selanjutnya dianalisis dengan uji korelasi Spearman Rank dan Chi-square. Nilai p uji Spearman Rank antara komorbid dengan lama rawat inap pasien post ORIF adalah 0,000. Nilai p uji Spearman Rank antara usia dengan lama rawat inap pasien post ORIF adalah 0,000. Nilai p uji Chi-square antara lokasi fraktur dengan lama rawat inap pasien post ORIF adalah 0,972. Nilai p uji Chi-square antara jenis fraktur dengan lama rawat inap pasien post ORIF adalah 0,031. Disimpulkan bahwa ada hubungan antara komorbid, usia, dan jenis fraktur dengan lama rawat pada pasien post ORIF.Kata kunci: komorbid; usia; lokasi fraktur; jenis fraktur; lama rawat inap; post ORIF